Bedouin Ethnobotany: Plant Concepts and Uses in a Desert Pastoral World - Narchi, Nemer E. (Ethnobiology Letters, 2013)
Review of Bedouin Ethnobotany: Plant Concepts and Uses in a Desert Pastoral World. James P. Mandaville. 2010. The University of Arizona Press, Tucson. Pp. 352, 33b/w photos, 2 maps, 5 tables. 55.00 (hardcover + CD). ISBN 978-0-8165-2900-1.